Incidence of two canals in extracted mandibular incisors teeth of Saudi Arabian samples - Khalid S Al-Fouzan; Abdulatif AlManee; Jilan Jan; Mansour Al-Rejaie (Wolters Kluwer Medknow Publications, 2012)
Aim: The purpose of this in vitro study is to provide clinical data on the presence of the second canal in mandibular incisor teeth of Saudi Arabian Samples. Materials and Methods: Eighty extracted human mandibular incisors were collected from Saudi patients. The teeth were accessed by small round bur then placed in 5.25% sodium hypochlorite for 24 hours to dissolve the organic debris. Indian ink was injected inside the root canal systems under negative pressure. The teeth were decalcified in 5% nitric acid for three days then dehydrated in different concentrations of ethyl alcohol. Following the decalcification process, the teeth were cleared in methyl salicylate and evaluated according to Vertucci's classification. Result: Fifty six of both mandibular central and lateral incisor teeth (70%) had type I canal configuration (one main canal and one main apical foramen), while the remaining 30% of the sample (24 teeth) had a type III canal configuration (two separate canals and merged into one canal before exiting the tooth through single apical foramen). Conclusion : The incidence of two canals in mandibular incisor teeth is about one third of the examined Saudi Arabian samples with no difference between the centrals and laterals. The clinician should deal with these teeth as if they have two canals unless it is proved otherwise.